Analysis of the Impact and Weight of Structural Parameters on the Operating Characteristics of the Spring Operating Mechanism - Qi Long; Xu Yang; Keru Jiang; Changhong Zhang; Xiao Wang; Xiongying Duan (IEEE Access)
The operational characteristics of high-voltage circuit breakers critically influence phase-controlled closing and power grid safety. To investigate the influence weights of structural parameters on the operational characteristics of the spring-operated mechanism and optimize its structure, the following steps were undertaken: First, a closing simulation model of the spring-operated mechanism used in a 252 kV circuit breaker was developed in Simulink to obtain the contact closing displacement curve. Second, the effects of different structural parameters on the closing time and velocity of the circuit breaker were examined. Third, a reliability model of the spring-operated mechanism was established, and a limit state function based on closing time was determined. By integrating the support vector machine surrogate model with the Monte Carlo reliability analysis method, the failure probability of the mechanism was determined, along with the specific influence weights of structural parameters on the operational characteristics of the spring-operated mechanism. Among these parameters, the spring preload has the greatest impact on the operational characteristics, accounting for approximately 28%, followed by the spring stiffness at 18%, and the output crank length at 15%. Finally, based on the influence weights, a sensitivity-adaptive particle swarm optimization algorithm was developed to optimize the spring-operated mechanism, reducing its failure probability by 16.67%, which is beneficial for the design of controlled switching algorithms.